Theta-frequency medial septal nucleus deep brain stimulation increases neurovascular activity in MK-801-treated mice - Crown, Lindsey M.; Agyeman, Kofi A.; Choi, Wooseong; Zepeda, Nancy; Iseri, Ege; Pahlavan, Pooyan; Siegel, Steven J.; Liu, Charles; Christopoulos, Vasileios; Lee, Darrin J. (Frontiers in Neuroscience, 2024)
Introduction Deep brain stimulation (DBS) has shown remarkable success treating neurological and psychiatric disorders including Parkinson’s disease, essential tremor, dystonia, epilepsy, and obsessive-compulsive disorder. DBS is now being explored to improve cognitive and functional outcomes in other psychiatric conditions, such as those characterized by reduced N-methyl-D-aspartate (NMDA) function (i.e., schizophrenia). While DBS for movement disorders generally involves high-frequency (>100 Hz) stimulation, there is evidence that low-frequency stimulation may have beneficial and persisting effects when applied to cognitive brain networks. Methods In this study, we utilize a novel technology, functional ultrasound imaging (fUSI), to characterize the cerebrovascular impact of medial septal nucleus (MSN) DBS under conditions of NMDA antagonism (pharmacologically using Dizocilpine [MK-801]) in anesthetized male mice. Results Imaging from a sagittal plane across a variety of brain regions within and outside of the septohippocampal circuit, we find that MSN theta-frequency (7.7 Hz) DBS increases hippocampal cerebral blood volume (CBV) during and after stimulation. This effect was not present using standard high-frequency stimulation parameters [i.e., gamma (100 Hz)]. Discussion These results indicate the MSN DBS increases circuit-specific hippocampal neurovascular activity in a frequency-dependent manner and does so in a way that continues beyond the period of electrical stimulation.